Ophthalmological research in Germany: suggestions by an international expert panel - Ader, Marius; Cursiefen, Claus; Fauser, Sascha; Gliem, Martin; Helbig, Horst; Lagrèze, Wolf; Marshall, John; Roesky, Christian; Sahel, José Alain; Schlötzer-Schrehardt, Ursula; Sieving, Paul; Ueffing, Marius (Die Ophthalmologie, 2024)
Purpose: To evaluate the research performance in ophthalmology in Germany based on the findings of the recent research map of the German Ophthalmological Society (DOG) and to suggest strategies for future improvements on a national level both to DOG as well as to politics. The focus is on preclinical and translational clinical research. Methods: International expert panel evaluation and discussion organized by the Task Force Research of the German Ophthalmological Society (DOG). Results: The international view on the German ophthalmological research landscape was generally positive. The value for money relationship was judged as very good. As Germany is facing an aging society and vision impairment will create an ever-increasing socioeconomic burden, the reviewers suggested several lines of future activities: an increased activity of securing intellectual property, more lay audience lobbying, intensified collaboration and critical mass building between “lighthouses” of ophthalmic research in Germany, as well as the establishment of a German national eye institute equivalent. Conclusion: The ophthalmological research performance in Germany was rated to be very good by an international expert panel. Nonetheless significant improvements were requested in the fields of translation (clinical trials, IP), synergy between specialized institutions and governmental funding for a German center for eye research.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Evaluation; Patent; Patient Advocacy Groups; Research; Vision